2020
DOI: 10.1213/ane.0000000000004528
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of Red Blood Cells, Fresh Frozen Plasma, or Platelets Is Associated With Mortality and Infection After Cardiac Surgery in a Dose-Dependent Manner

Abstract: BACKGROUND: It is unclear whether transfusion of platelets or fresh frozen plasma, in addition to red blood cells, is associated with an increased risk of mortality and infection after cardiac surgery. METHODS: Patients who underwent valve surgery and/or coronary artery bypass grafting from January 1, 2011 to June 30, 2017 and September 1, 2013 to June 30, 2017 at 2 centers performing cardiac surgery were included in this retrospective study. After stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Several other studies reported similar associations of PLT transfusion in a variety of patient populations. PLT transfusion has been shown to be significantly associated with increased infection in patients undergoing cardiac surgery [32]. In a study of 511 children requiring ECMO, their findings were quite similar to our study for PLT transfusion and its association with mortality [33].…”
Section: Discussionsupporting
confidence: 87%
“…Several other studies reported similar associations of PLT transfusion in a variety of patient populations. PLT transfusion has been shown to be significantly associated with increased infection in patients undergoing cardiac surgery [32]. In a study of 511 children requiring ECMO, their findings were quite similar to our study for PLT transfusion and its association with mortality [33].…”
Section: Discussionsupporting
confidence: 87%
“…These deaths, according to a recent study, may include deaths from infection, bleeding, and cardiovascular issues 19 . Indeed, transfusion of RBCs has been shown to be an independent risk factor of infection and mortality 62 …”
Section: Discussionmentioning
confidence: 99%
“…Although the only case with mortality was observed in obese patients, this difference was not significant and the perioperative variables for this specific patient was similar with non obese patients and no technical issue was experienced. Bleeding and amount of blood transfusions were also similar which are important in limiting overall and infection‐specific adverse events 13,14 . Reser et al 15 who have compared their patients of different BMIs undergoing minimally invasive mitral surgery observed increased ventilation times in their patients with BMI > 30, which did not result in increased adverse events nonetheless.…”
Section: Discussionmentioning
confidence: 96%